2005
DOI: 10.1038/sj.npp.1300949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atypical Antipsychotic Drugs on Intralipid Intake and Cocaine-Induced Hyperactivity in Rats

Abstract: Clozapine and olanzapine have been shown to acutely stimulate consumption of a fat emulsion (Intralipid) by male Lister hooded rats. We initially investigated the extent of any sex difference in Intralipid hyperphagia associated with olanzapine treatment. We then examined the degree of Intralipid hyperphagia produced by a range of atypical antipsychotic drugs having different associations with human weight gain, and also determined their effects on cocaine-stimulated locomotor activity as a measure of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…Studies in rodents have consistently failed to demonstrate increased food intake following ZIP treatment (Fell et al 2005a;Fell et al 2007;Fell et al 2008;Hartfield et al 2006;Kirk et al 2004;MinetRinguet et al 2006a;Park et al 2012;Shobo et al 2011b;Snigdha et al 2008;von Wilmsdorff et al 2010). Negative findings occur regardless of sex, method of drug administration, time of drug administration relative to outcome measured, or dose range.…”
Section: Aripiprazole and Ziprasidonementioning
confidence: 84%
See 3 more Smart Citations
“…Studies in rodents have consistently failed to demonstrate increased food intake following ZIP treatment (Fell et al 2005a;Fell et al 2007;Fell et al 2008;Hartfield et al 2006;Kirk et al 2004;MinetRinguet et al 2006a;Park et al 2012;Shobo et al 2011b;Snigdha et al 2008;von Wilmsdorff et al 2010). Negative findings occur regardless of sex, method of drug administration, time of drug administration relative to outcome measured, or dose range.…”
Section: Aripiprazole and Ziprasidonementioning
confidence: 84%
“…In a similar fashion to CLO, dosing paradigms directly administering OLA acutely prior to measurements of food intake consistently demonstrate increased food consumption regardless of rodent sex (Hartfield et al 2003;Hartfield et al 2006;Kirk et al 2004;Shobo et al 2011b) and with OLA administration peripherally as well as centrally. However, studies examining repeated/ chronic dosing paradigms of OLA show interesting sex differences.…”
Section: Clozapinementioning
confidence: 87%
See 2 more Smart Citations
“…Tschoner et al found higher fasting glucose and an increased score in an insulin resistance model in patients treated with olanzapine, while this effect could not be observed in ziprasidone treated patients, indicating the involvement of this effect in olanzapine-induced weight gain 6 . Animal studies have shown that olanzapine, but not ziprasidone, stimulates the consumption of fat 36 and that chronic treatment with olanzapine impairs lipolysis by adipocytes 37 . Also, previous studies have found cholesterol, triglycerides and LDL-cholesterol increase in olanzapine treated patients, and not in ziprasidone treated individuals 6,38 .…”
Section: Discussionmentioning
confidence: 99%